“That Poem Was Pretty Wild to Me”: On Personal Safety and Precarious Moments in Teacher Candidates’ Responses to Sexual Assault Narratives - Moore, Amber (Research in the teaching of English, 2025)
Please note that some discussions of domestic, sexual, and racial violence are included in this article. This article explores how teachers and students in a teacher training program constructed precarious moments by engaging with sexual assault literature and pedagogy that centers rape culture and sexual trauma. In this qualitative feminist study, 23 participants took up readings of a sexual trauma text set and responded to pedagogy for teaching such texts with adolescent students in the Canadian K-12 public school system. A focal aim of this project is to think ahead to how teachers in training might cultivate radical communities prepared to address the pervasiveness of sexual assault and the insidiousness of rape culture in the secondary English classroom. As such, the ways in which teacher candidates’ experiences of and witnessing precarious personal safety, as well as how precarious moments impacted their attitudes toward considering this pedagogy in particular, are analyzed.